Cyclical crisis of capitalist development in the periphery : A reading from Argentina - Féliz, Mariano (2005)
Explaining the recurrence of crisis in Argentina under the form of balance of payment difficulties requires an answer to the question of why the real exchange rate does not tend to correct the external imbalances as should happen according to the neoclassical explanation. That is, why does the real exchange rate tend to move, systematically, towards values that make the result of the current account of the balance of payments unsustainable? In synthesis, why does the real exchange rate in Argentina tends to over-value in relation to the 'needs' of the balance of payments, if over-valuation expresses the impossibility of equilibrating it? In this article we will show that it is Argentina's economic structure that generates this behavior. We will do so by combining three tools of analysis: the concept of 'des-equilibrated productive structure'; a model of 'structural' real exchange rate determination; and the effects of existence of rent from natural resources (typical of semi-industrialized Latin-American economies). With these ideas in mind we will show how structural forces act in the short- and long-run, emphasizing the fact that the effects of devaluation in peripheric economies are of a different qualitative nature as those in developed (center) economies. We will end our presentation with a few reflections on the contradictions and policy decisions that this economic structures pose.